Engendering the illicit: female agency and "bad women" in Malaya and Singapore, 1900-1956 - Fong, Alison Min (Nanyang Technological University, 2024)
This study challenges patriarchal narratives on the role of women during the Japanese Occupation of Malaya and Singapore and the early Malayan Emergency by examining how women from lower socio-economic classes navigated and subverted colonial and postcolonial authority. Faced with limited economic opportunities, these women participated in illicit activities—smuggling, black market trading, and resistance—as strategies for survival. Their actions complicate the dominant portrayal of women as passive victims or self-sacrificial heroines, revealing instead a nuanced agency that redefined societal norms. Focusing on marginalized actors erased from official narratives, this research interrogates how these women's economic roles intersected with broader histories of mid-twentieth-century Singapore and Malaya. By analyzing the moral ambiguities of their actions, the study explores how their participation in illicit economies challenged gendered limitations and illuminated intersections of maternalism, feminism, and individualism. These narratives offer a female-centered perspective on the socio-political and economic transformations of the era, reshaping how we understand the intersections of survival, resistance, and state power.